(untitled) (Polish Yearbook of International Law, 2025)
The principle of non-intervention belongs amongst the most often discussed rules of international law with the potential to regulate cyber information (dis- and misinformation) operations carried out by one state and dedicated to influence another state’s elections results (through the electorate). Contributions to those discussions differ significantly however as to the suitability of the rule for this purpose. This article tackles the issue in a step-by-step analysis, first dealing with the elements of the principle of non-intervention and its position in the systematics of the law of international peace and security, secondly analysing the applicability of the rule in cyberspace, in order to thirdly determine and evaluate what are the critical issues in the application of the rule to cyber information operations targeting the electorate of another state. Because the principle belongs to the most approximate rules of international peace and security regulation to tackle these operations, the last section is dedicated to recommendations that if applied, they might increase the likelihood of the applicability of the principle of non-intervention to the operations discussed.